Analysis of Tools to Evaluate Chloride Threshold for Corrosion Onset of Reinforced Concrete in Tropical Marine Environment of Yucatán, México - Pedro Castro-Borges; Mercedes Balancán-Zapata; Alexander López-González (Journal of Chemistry)
The chloride threshold for corrosion onset of reinforced concrete depends on several factors and is only valid for the specific condition of each factor. The main objective of this paper was to analyze different tools to obtain the chloride threshold for corrosion onset of reinforced concrete in tropical marine environment. Sixty Portland cement concrete cylinders were exposed in a tropical marine environment. One half of the samples had a reinforcing bar embedded at the center of the sample (corrosion measurements), and the other half was made with plain concrete (chloride measurements). Five water/cement ratios were tested representing the common practices of this region. The corrosion rate was monitored using the polarization resistance technique, and the chloride content was determined using an ion selective electrode. The chloride threshold was in the range of 0.3% to 1.1% by weight of cement for specimens at 50 m from the seashore. Main conclusion indicates that iaccum is a better tool to determine and/or predict chloride threshold in this study according to a conservative point of view in civil engineering. Using this tool, chloride threshold was 0.26% to 0.73% by weight of cement.